Investigation on thermal property parameters characteristics of rocks and its influence factors - Jian Xiong; Haiyu Lin; Huaishuo Ding; Haocheng Pei; Chenggan Rong; Wenhai Liao (Natural Gas Industry B, 2020)
In this paper, the thermal property parameters of rocks from different lithology were studied with the cores from the different formation in Sichuan Basin and Tarim Basin as the research objects. The influences of mineral composition, density, porosity and other factors on the thermal property parameters of rocks were analyzed. The acoustic response laws of the thermal property parameters of rocks were discussed, and the prediction models of the thermal property parameters of rocks were built. The results show that the lithology has obvious influence on the thermal conductivity and the thermal diffusion coefficient of rocks, whereas the lithology has little influence on the specific heat capacity of rocks. The clay minerals have a negative effect on the thermal conductivity and the thermal diffusion coefficient of rocks, whereas the quartz has a positive effect on the thermal conductivity and the thermal diffusion coefficient of rocks. And the clay minerals and quartz have no obvious effect on the specific heat capacity of rocks. The thermal conductivity and thermal diffusion coefficient of rocks are positively correlated with the density and the P-wave velocity, whereas there is a negative relationship between the thermal conductivity and the thermal diffusion coefficient of rocks and the porosity. And the specific heat capacity of rocks has a weak negative correlation with the density and the P-wave velocity, whereas the specific heat capacity has a weak positive correlation with the porosity. Based on the geophysical logging method, the prediction models of the thermal property parameters of rocks are established, which have a good prediction effect on the rock thermal property parameters.